Evaluation of Abnormal Cervix with Visual Inspection under Acetic Acid and Colposcopy - Bhattachan, Kabin; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Parajuli, Sharmila; Poudel, Rekah; Bajracharya, Nishma; Tiwari, Kenusha (Journal of Nepal Health Research Council, 2019)
Background: Cervical cancer is a major public health problem especially in developing countries. It can be prevented through implementation of routine screening program. There are different screening methods but their efficacy are still questionable. So the purpose of this study is to evaluate the efficacy of visual inspection of cervix with acetic acid and colposcopy to detect precancerous lesion in women with clinically unhealthy or abnormal cervix. Methods: Forty patients with abnormal cervix (35) and abnormal pap smear results (5) were enrolled for the study in outpatient department of Kathmandu Model Hospital. Patients were evaluated with visual inspection of cervix with acetic acid and colposcopy in the same sitting. Cervical punch biopsy were taken from suspected lesion or from four quadrant if colposcopy findings were normal and sent for histopathological examination. The finding of visual inspection of cervix with acetic acid and colposcopy were correlated with histopathological finding and compared with each other. Results: The age of participants ranged from 24 to 68 years with mean age of 38.17 years and mean parity of 2.25. visual inspection of cervix with acetic acid and colposcopy were positive in eight (20%) and ten (25%) respectively. There were five (12.5%) cases of histopathologically proven lesion. The sensitivity of visual inspection of cervix with acetic acid and colposcopy were 80% and 100 % respectively and that of specificity were 88.5% and 85.5%. Conclusions: visual inspection of cervix with acetic acid is an effective screening tool with comparable sensitivity and specificity. It can be used as alternative screening methods especially in low income resource countries where the burden of disease is high. Keywords: Cervical cancer; Colposcopy; screening; VIA.